IMPLEMENTASI SISTEM AKUNTANSI SEDERHANA (SAS) DITINJAU DARI TAM (TECHNOLOGY ACCEPTANCE MODEL) PADA KELOMPOK SWADAYA MASYARAKAT (KSM) YANG TERGABUNG DALAM PROGRAM PENINGKATAN PENGHIDUPAN MASYARAKAT BERBASIS KOMUNITAS (PPMK) PNPM MANDIRI PERKOTAAN - B41111119, Widiana widi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
IMPLEMENTASI SISTEM AKUNTANSI SEDERHANA (SAS) DITINJAU DARI TAM  (TECHNOLOGY ACCEPTANCE MODEL) PADA KELOMPOK SWADAYA MASYARAKAT (KSM) YANG TERGABUNG DALAM PROGRAM PENINGKATAN PENGHIDUPAN MASYARAKAT BERBASIS KOMUNITAS (PPMK) PNPM MANDIRI PERKOTAAN Abstract            This study aims to determine the design and implementation of Simplified Accounting System (SAS) on the Self Help Groups (SHGs). Self-Help Groups (SHGs) which is used as a sample object that is incorporated in Program Improvement based Livelihoods Community (PILC) PNPM Urban. In addition, this study also aims to determine the application of Simplified Accounting System (SAS) on the Self Help Groups (SHGs) in terms of TAM (Technology Acceptance Model).            Results of this study was the presentation of Simplified Accounting System (SAS) which is used by SHGs in conducting financial records will be reported to the PNPM Urban. Not all SHGs implement SAS because members do not have sufficient time to implement SAS. Judging from TAM (Technology Acceptance Model) all agree that KSM helpful SAS (perceived usefulness) in the financial records, while based on the ease (perceived ease of use) is only partially KSM stating SAS easy to use in financial records.Keywords: Simple Accounting System (SAS), Self-Help Groups (SHGs), perceived       usefulness, perceived ease of use